HUBUNGAN INTERAKSI SOSIAL DENGAN KONSEP DIRI DALAM MEMAHAMI ATURAN PADA SISWA KELAS XI SMK NEGERI 7 MEDAN - Dimas Budi Prabawa; Nurul Azmi Saragih; Ika Sandra Dewi; Nur Asyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to determine whether there is a relationship between social interaction and self-concept in understanding rules among students. Social interaction is a dynamic relationship that brings people together, groups with groups, and individuals with human groups. Whereas self-concept is an individual's perception of themselves based on what is actually happening and what they want to happen. The research method used in this study is quantitative research using a correlational research design. The population in this study consists of all 200 students in class XI at SMK Negeri 7 Medan. The sample size is 35 students, selected using the simple random sampling technique, which involves random selection. The instruments used were a social interaction questionnaire and a self-concept questionnaire, using a likert scale with a checklist format. The Cronbach's Alpha value for the social interaction questionnaire is 0.925, and for the self-concept questionnaire, it is 0.871, indicating reliability. The results of the hypothesis testing yielded a correlation coefficient of 0.529, which falls within the coefficient interval of 0.40-0.599, indicating a moderate level of relationship. The significance (p) was 0.000 < 0.05, meaning the two variables have a positive relationship. The results of the coefficient of determination show that the calculated value of R Square is 0.280, which means that 28% of self-concept is influenced by social interaction. Meanwhile, 72% of self-concept is influenced by several factors, namely competence, physical, feelings, self-actualization, virtue, and parents.